Update on the clinical utility of once-daily tacrolimus in the management of transplantation - Posadas Salas MA; Srinivas TR (Dove Medical Press, 2014)
Maria Aurora Posadas Salas, Titte R Srinivas Division of Nephrology and Hypertension, Department of Medicine, Medical University of South Carolina, Charleston, SC, USA Abstract: Adherence to immunosuppression and minimizing variability in drug exposure are important considerations in preventing rejection and maximizing overall transplant outcomes. The availability of once-daily tacrolimus may confer potential benefit by simplifying immunosuppressive regimens, thereby improving medication adherence among transplant recipients. Pharmacokinetic studies in healthy normal volunteers and stable transplant recipients suggest that once-daily tacrolimus is bioequivalent to twice-daily tacrolimus. Efficacy studies suggest that once-daily tacrolimus is noninferior to twice-daily tacrolimus with a concentration-dependent rejection risk. The incidence of biopsy-proven acute rejection, graft survival, and patient survival are more or less comparable between the two tacrolimus formulations. Once-daily tacrolimus has also been reported to have favorable effects on blood pressure, lipid profile, and glucose tolerance. Once-daily tacrolimus may be a viable option to consider for de novo immunosuppression or for conversion from conventional tacrolimus. Keywords: pharmacokinetics, toxicity, immunosuppression, adherence